THE MEDIATION ROLE OF PERCEIVED QUALITY AND PRICE ON THE INFLUENCE OF COUNTRY OF ORIGIN IMAGE ON PURCHASE INTENTION (Study of Sunscreen Innisfree in Denpasar City) - Ketut Ari Satya Utami; Putu Saroyini Piartrini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The appeal of beauty products among today's teenagers has encouraged skincare products from various countries to enter the Indonesian market. The beauty products most widely used by Indonesian women are products made in Korea. Sunscreen is the most popular type of skin care in Denpasar City. A business phenomenon was found which was indicated by a decline in sales of Innisfree products and was followed by a lack of purchase intention for Innisfree sunscreen products in Denpasar City. This research aims to predict the influence of country of origin image on Innisfree sunscreen purchase intention from a Signaling Theory perspective, taking into account perceived quality and price. The survey data used in this research was 120 respondents in Denpasar City using a purposive sampling method. The results of path and sobel analysis reveal that country of origin image has a positive and significant effect on purchase intention, country of origin image has a positive and significant effect on perceived quality, country of origin image has a positive and significant effect on price, perceived quality has a positive and significant effect on purchase intention, price has a positive and significant effect on purchase intention, perceived quality positively and significantly mediates the effect of country of origin image on purchase intention, and price positively and significantly mediates the effect of country of origin image on purchase intention of Innisfree sunscreen consumers in Denpasar City. The results of this research provide implications for developing business strategies to pay more attention to purchase intention by considering country of origin image, perceived quality, price. It is recommended that further research test the consistency of the findings by including the luxury brand perception variable in the conceptual model.